In vivo N-Terminomics Highlights Novel Functions of ADAMTS2 and ADAMTS14 in Skin Collagen Matrix Building - Leduc, Cédric; Dupont, Laura; Joannes, Loïc; Monseur, Christine; Baiwir, Dominique; Mazzucchelli, Gabriel; Deroanne, Christophe; Colige, Alain; Bekhouche, Mourad (Frontiers in Molecular Biosciences, 2021)
ADAMTS2 and ADAMTS14 were originally known for their ability to cleave the aminopropeptides of fibrillar collagens. Previous work using N-terminomic approach (N-TAILS) in vitro led to the identification of new substrates, including some molecules involved in TGF-β signaling. Here, N-TAILS was used to investigate the substrates of these two enzymes in vivo, by comparing the N-terminomes of the skin of wild type mice, mice deficient in ADAMTS2, in ADAMTS14 and in both ADAMTS2 and ADAMTS14. This study identified 68 potential extracellular and cell surface proteins, with the majority of them being cleaved by both enzymes. These analyses comfort their role in collagen matrix organization and suggest their implication in inflammatory processes. Regarding fibrillar collagen, this study demonstrates that both ADAMTS2 and ADAMTS14 are involved in the processing of the aminopropeptide of alpha1 and alpha2 type V collagen. It also revealed the existence of several cleavage sites in the Col1 domain and in the C-propeptide of type I collagens. In addition to collagens and other extracellular proteins, two major components of the cell cytoskeleton, actin and vimentin, were also identified as potential substrates. The latter data were confirmed in vitro using purified enzymes and could potentially indicate other functions for ADAMTS2 and 14. This original investigation of mouse skin degradomes by N-terminomic highlights the essential role of ADAMTS2 and ADAMTS14 in collagen matrix synthesis and turnover, and gives clues to better understand their functions in skin pathophysiology. Data are available via ProteomeXchange with identifier PXD022179.